Resistance of Dairy Cows During the Use of New Production Fodder - Kolesnikov , Roman; Morozov, Vitaly; Matserushka, Anna; Talalay, Galina; Kolesnokova, Margarita (KnE Life Sciences, 2021)
This paper examines the development of a fundamentally new automated hydroponic system for growing green fodder, which creates a solid fodder base capable to satisfy the need of livestock for nutrients throughout the year with low material costs. The new hydroponic green fodder produced according to the developed technology contained the required nutrients that contribute to the digestion of proteins, fats and carbohydrates into easily digestible organic components (amino acids, fatty acids and simple sugars) which are simpler in their structure. Moreover, it completely replaced compound feed, a mineral supplement in the diet of milking cows, and reduced the amount of fodder needed. In dry matter, compared to fodder barley, the content of protein (128.93%) and fat (196.73%) were higher, and biologically active substances were also formed. The new fodder used the nutrients of the diet more efficiently, increased milk production and reduced fodder costs. When hydroponic green fodder from barley was introduced into the diet of cows with 100% replacement of the compound fodder and 50% replacement of grain mass, milk yield in the experimental group exceeded the yield in the control group by 6%. An additional 549.5 kg was obtained from each cow for lactation, and 549.5 × 20 = 10990 kg was obtained from the entire experimental group. The annual income from feeding green fodder was 329710 rubles at the purchase price of milk of 30 rubles / kg (10990 × 30), and the daily efficiency of compound fodder was (80.6 × 20) = 1612 rubles; for the period of lactation it was 491660 rubles. Keywords: technology, new fodder, productivity, milk quality, resistance